Strategi Hubungan Pelanggan dalam Membangun Persepsi Citra Merek di Kalangan Generasi Z pada Brand Gozeal - Ridho Rahmatulloh; Arfian Suryasuciramdhan; Muhamad Sobahri; Alif Kusuma Wardana (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
This study aims to explore the Customer Relationship Management (CRM) strategies implemented by Gozeal, a local Indonesian fashion brand, in shaping a positive brand image among Generation Z. Using a descriptive qualitative approach, data were collected through interviews, social media observation, and digital documentation. The findings indicate that Gozeal effectively builds emotional engagement through two-way digital interactions, relevant storytelling, collaborations with influencers, and community-based activities. These strategies have successfully shaped a brand image perceived as creative, trendy, and communicative—aligned with Generation Z’s values such as originality, self-expression, and participation. The study emphasizes the importance of authentic, personalized, and interactive marketing approaches in fostering brand loyalty and a positive brand perception in the digital era.